The Effect of Resveratrol on Radioiodine Therapy-Associated Lacrimal Gland Damage. (4th March 2021) - Koca, Gökhan; Singar, Evin; Akbulut, Aylin; Yazihan, Nuray; Yumuşak, Nihat; Demir, Ayten; Korkmaz, Meliha
ABSTRACT: Purpose: We have evaluated the potential radioprotective, antioxidant and anti-apoptotic effects of resveratrol (RSV) against high-dose radioactive iodine (RAI) therapy associated damage of the lacrimal glands by biochemical, histopathological and immunohistochemical methods. Materials and Methods: Thirty Wistar-albino rats were randomly divided into three groups; the control group received no treatment or medication, the RAI group received RAI but no medication and the RSV group received oral RAI and intraperitoneal RSV. RSV was started at day one, before RAI administration, and continued for 8 days. Bilateral intraorbital (IG), extraorbital (EG), and Harderian (HG) lacrimal glands were evaluated in all rats for histopathological, immunohistochemical, tissue cytokine and oxidant and antioxidant level assessment. Results: RSV group restored inflammation, fibrosis, vacuolization, change in nucleus characteristics, lipofuscin-like accumulation and cellular morphologic patterns were statistically significant in all lacrimal gland types, compared to the RAI group ( p < .05 for all variables). Similarly, elevated Caspase-3 and TUNEL levels in the RAI group were significantly alleviated in the RSV group in all lacrimal gland types ( p < .05 for all variables). RAI administration significantly elevated TNF-α, IL-6, NF-кb levels, and decreased IL-10 levels ( p < .05 for all parameters) whereas TOS levels significantly increased and TAS levels were significantly decreased. However, RSV significantly diminished TNF-α, IL-6, IL-4, and NF-кb levels. Furthermore, RSV significantly decreased TOS and increased TAS levels ( p < .05 for all variables). Conclusions: We conclude that with its anti-cancer effect as well as its antioxidant effect RSV has protected the histopathological pattern of the lacrimal glands from the damage, decreased inflammation in histopathologic assessments, and decreased tissue cytokine levels, apoptosis and DNA fragmentation on the lacrimal glands after RAI.